Role of tumor associated macrophages in tumor angiogenesis and lymphangiogenesis - Kzhyshkowska, Julia; Riabov, Vladimir; Gudima, Alexandru; Wang, Nan; Orekhov, Alexander; Mickley, Amanda (Frontiers in Physiology, 2014)
Tumour angiogenesis is an essential process for supplying rapidly growing malignant tissues with essential nutrients and oxygen. An angiogenic switch allows tumour cells to survive and grow, and provides them access to vasculature resulting in metastatic disease. Monocyte-derived macrophages recruited and reprogrammed by tumour cells serve as a major source of angiogenic factors boosting the angiogenic switch. Tumour endothelium releases angiopoietin-2 and further facilitates recruitment of TIE2 receptor expressing monocytes (TEM) into tumor sites. Tumour-associated macrophages (TAM) sense hypoxia in avascular areas of tumours, and react by production of angiogenic factors such as VEGFA. VEGFA stimulates chemotaxis of endothelial cells (EC) and macrophages. In some tumours, TAM appeared to be a major source of MMP9. Elevated expression of MMP9 by TAM mediates extracellular matrix degradation and the release of bioactive VEGFA. Other angiogenic factors released by TAM include bFGF, thymidine phosphorylase (TP), urokinase-type plasminogen activator (uPA), and adrenomedullin. The same factors used by macrophages for the induction of angiogenesis (like VEGF-A and MMP9) support lymphangiogenesis. TAM can express LYVE-1, one of the established markers of lymphatic endothelium. TAM support tumour lymphangiogenesis not only by secretion of pro-lymphangiogenic factors but also by trans-differentiation into lymphatic EC. New pro-angiogenic factor YKL-40 belongs to a family of mammalian chitinase-like proteins (CLP) that act as cytokines or growth factors. Human CLP family comprises YKL-40, YKL-39 and SI-CLP. Production of all three CLP in macrophages is antagonistically regulated by cytokines. It was recently established that YKL-40 induces angiogenesis in vitro and in animal tumour models. YKL-40-neutralizing monoclonal antibody blocks tumour angiogenesis and progression. The role of YKL-39 and SI-CLP in tumour angiogenesis and lymphangiogenesis remains to be investigated.